Colorless and unidirectional diffractive-type solar concentrators compatible with existing windows - Dewei Zhang; Zhenghao Guo; Chun-Ting Xu; Jianqing Li; Yan-Qing Lu; Wei Hu (PhotoniX)
Abstract Solar concentrators laterally converge solar energy to the side of architectural glass and are attractive candidates for building-integrated photovoltaics. Present available luminescent-type and scattering-type solar concentrators suffer from omnidirectional waveguide induced low efficiency, coloring/hazing restrained aesthetic quality, and poor compatibility with existing architectural glass. Here, we propose a diffractive solar concentrator via directly coating cholesteric liquid crystal (CLC) layers onto the architectural glass. The stacked CLC layers with submicron lateral periodic alignment enable broadband and unidirectional waveguiding inside the glass, and thus supply a high-efficient platform for transmissive solar energy capturing with merits of high aesthetic quality and economic viability. A 1-inch-diameter prototype powers a 10-mW fan outdoors, and a typical 2-m-wide window is calculated to concentrate solar energy by 50 times. The design is expected to bring a global terawatt-scale green energy supply and billion-ton annual carbon emission reduction, meeting with the sustainable development of human society.